D. Z. Phillips on the grammar of “God” - Min, Anselm Kyongsuk (International journal for philosophy of religion, 2008)
In this essay dedicated to the memory of D. Z. Phillips, I propose to do two things. In the first part I present his position on the grammar of God and the language game in some detail, discussing the confusion of “subliming” the logic of our language, the contextual genesis of sense and meaning, the idea of a world view, language game, logic, and grammar internal to each context, the constitution of the religious context, and the grammar of God proper to that context. In the second part I present my appreciative critical reflection by arguing that the conception of context and language game must be made more dialectical, that the grammar of God needs more systematic metaphysical analysis, and that a greater sense of the radical transcendence of God over a language game is necessary in order to avoid reductionism always inherent in any contextual approach.